Modified SLM algorithm based on cyclic shift and signal combination in MIMO-OFDM system - Wu-jun HU; Lin YANG (Tongxin xuebao)
In order to reduce the computational complexity of conventional selective mapping (SLM) algorithm in multiple input multiple output orthogonal frequency division multiplexing (MIMO-OFDM) system，more candidate sequence sets will be produced.With different peak to average power ratio (PAPR) by time domain cyclic shift and signal combination between the antennas.The receiving part can restore the rotation signals by using the sequence selection order of the transmitting part and also the original signals by comparing the inversed rotation sequence with its nearest constellation points.The simulation results show that the proposed method can effectively reduce the PAPR of OFDM signals.In addition，compared with the conventional SLM algorithm，the proposed method can reduce the algorithm computation complexity significantly and obtain similar bit error rate (BER) performance.